Assistance for the Improvement of Water Quality Status and Fertility Level of Water Site Patok, Mundu District, Cirebon District - Muktar; Agus Sugiarto (PT FORMOSA CENDEKIA GLOBAL, 2022)
Utilization of Situ Patok in Cirebon Regency has a strategic function in meeting the needs of people's lives, including in the fields of fisheries, agriculture, and household needs such as washing and bathing. The status of water quality and the level of fertility of the waters in Bengawan Jero need to be known so that the management of the waters in the area is sustainable and sustainable in order to create community welfare. This research was conducted in July 2017 in Turi District. The method used is a logical descriptive method with analysis of water quality status data using the STORET method based on the Minister of Environment Decree No. 115 of 2003 and the Carlson Trophic State Index (TSI) to determine the level of water fertility. Based on the results of the study, the quality status of Situ Patok was in poor condition (heavy polluted) in Class I and II, while in class III it was in moderate condition (moderately polluted). The level of fertility of the waters in the Situ Patok Bendungan has been in a hypereutrophic condition or a condition where the nutrients are very high. So it is necessary to overcome eutrophication by one way of spreading plankton-feeding fish (plankton feeders).